Ethnicity and Health in Colombia: What Do Self-Perceived Health Indicators Tell Us (2016)
ABSTRACT: Objective: To compare self-perceived health indicators between ethnic groups in Colombia. Methods: Cross-sectional study with data from the 2007 National Public Health Survey (ENSP-2007). Data from 57,617 people ≥18 years were used. Variables included: belonging to an ethnic group (exposure); self-rated health; mental health problems, injuries for accidents/violence (outcomes); sex, age, education level and occupation (explicative/control). A descriptive study was carried out of the explicative variables, and the prevalence of the outcomes was calculated according to ethnicity, education level and occupation. The association between the exposure variable and the outcomes was estimated by means of adjusted odds ratios (OR) with 95% CI using logistic regression. Analyses were conducted separately for men and women. Results: The prevalence of outcomes was higher in people reporting to belong to an ethnic group and differences were found by sex, ethnic groups and health outcomes. Women from the Palenquero group were more likely to report poor self-rated health (aOR 7.04; 95%CI 2.50-19.88) and injuries from accidents/violence (aOR 7.99; 95%CI 2.89-22.07). Indigenous men were more likely to report mental health problems (aOR 1.75; 95%CI 1.41-2.17). Gradients according to ethnicity, education, occupation and sex were found. Conclusions: Minority ethnic groups are vulnerable to reporting poor health outcomes. Political actions are required to diminish health inequalities in these groups.